Peran Inovasi dalam Kewirausahaan Berbasis Teknologi Informasi: Analisis Literatur Menggunakan Teknik PRISMA - Wirdawati, Wira; Veri, Jhon (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to identify and analyze the role of innovation in the development of information technology (IT)-based entrepreneurship through a systematic literature review (SLR) approach with the Prisma technique and analyze the role of innovation in supporting the success of information technology-based entrepreneurship through a systematic literature review approach with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) technique. Innovation is a key factor in creating competitive advantage, expanding the market, and increasing the sustainability of Information Technology businesses in the digital era. Innovation is considered a key factor in developing new products, services, and business models that are relevant to the dynamics of the digital market. This study identifies and reviews a number of scientific publications published in the period 2023–2025, obtained through the Scopus, IEEE Xplore, and Google Scholar databases. The results of the study show that innovation plays an important role in increasing the competitiveness, adaptability, and sustainability of Information Technology-based businesses. These findings also reveal that collaboration factors, digital ecosystem support, and adoption of cutting-edge technology are the main drivers of the success of innovation in Information Technology entrepreneurship.